OPTIMALISASI PENGGUNAAN MEDIASI SEBAGAI SALAH SATU CARA PENYELESAIAN SENGKETA - TITIN APRIANI (Universitas Mahasaraswati K. Mataram, 2022)
The purpose of this study is to find out how to optimize the use of mediation as a way of resolving disputes, either through mediation in court or mediation outside the court. This research is a libraryresearch that uses data in the form of books, laws, articles, journals and other literature related to the title, while the technique and data collection is to collect various ideas, theories and concepts from various literatures that focus on whether the use of mediation as a way of resolving disputes can be said to be optimal or not good, so it is necessary to add a legal basis or legislation, especially mediation outside the court to be more optimal. The approach method used in this research is the statutory approach and the conceptual approach. The results showed that the optimization of dispute resolution through mediation was not fully optimal due to its low success rate. This is due to obstacles, both in court and out of court mediation